The rebel's silhouette : selected poems - Faiz, Faiz Ahmad, 1911- (University of Massachusetts Press, 1995)
Born in India and considered the leading poet on the South Asian subcontinent, Faiz Ahmed Faiz (1911-1984) was a two-time Nobel nominee and winner of the 1962 Lenin Peace Prize. His evening readings in Hindi/Urdu-speaking regions drew thousands of listeners. Associated with the Communist party in his youth, Faiz became an outspoken poet in opposition to the Pakistani government. He was also a professor of English literature, a distinguished editor and a major figure in the Afro-Asian writer's movement. This volume offers a selection of Faiz's poetry in a bilingual Urdu/English edition with a new introduction by poet and translator Agha Shahid Ali.